A new antifungal phenolic glycoside derivative and iridoids and lignans from Alibertia sessilis (Vell.) K. Schum. (Rubiaceae) - Silva, Viviane C. da [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Young, Maria C. M.; Lopes, Márcia Nasser [UNESP] (FapUNIFESP (SciELO), 2007)
A new antifungal phenolic glycoside, 3,4,5-trimethoxyphenyl-1-O-β-D- (5-O-syringoyl)-apiofuranosyl-(1→6)-β-D-glucopyranoside (1), together with four known iridoids, geniposidic acid (2), geniposide (3), 6α-hydroxygeniposide (4) and 6β-hydroxygeniposide (5); two lignans, (+)-lyoniresinol-3α-O-β-D-glucopyranoside (6), (-)-lyoniresinol- 3α-O-β-D-glucopyranoside (7); and two phenolic acids, chlorogenic (8) and salicylic acids (9) and D-manitol (10), were isolated from the ethanolic extract of the stems of Alibertia sessilis. Structures of 1 and of the known compounds were determined by spectroscopic analysis. All compounds isolated were evaluated for their antifungal activities against two phytopathogenic fungi strains Cladosporium cladosporioides and C. sphaerospermum by direct bioautography. ©2007 Sociedade Brasileira de Química.
Keywords: Alibertia sessilis; Antifungal; Iridoids; Phenolics; Rubiaceae